Property right in the economical and legal perspective - Shcherbakova, Yekaterina (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims an analysis of the property right law system in the civil law of the Russian Federation. Presenting the construction of the right to property the author take into consideration both the economical and legal perspective.
Keywords: property right; civil right; economical perspective; legal perspective